Dynamic systems as affected by fast random disturbances - Skorokhod А. V. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Dynamical systems, depending on a randomly varying parameter, are considered. Conditions, under which such a dynamical system turns into a diffusion process, are investigated.